REGIONAL DIALECT MAPPING: LINGUOGEOGRAPHIC APPROACH - Yakubov Sadigjon Latif o‘g‘li (International Journal of Literature and Language Studies, 2026)
Annotation. In this article, the issue of drawing up a linguistic map of territorial dialects is analyzed on the basis of a linguistic approach. The author shows ways to map them, comparing the lexical, phonetic and grammatical features of dialects and dialects formed in different regions. The study was conducted at the intersection of language geography, dialectology and modern information technology, highlighting effective methods of visual rendering of dialectal differences. This approach contributes to a deeper understanding of the internal systems of the national language.